The Pedagogical Approach and its Role - Bazarova Shohida Ashirkulovna (Zien Journals, 2023)
Communication is manifested in conjunction with the social needs that arise as a result of the spiritual basis of human activity. It also has a significant impact on the formation of interpersonal relationships, the culture of communication.
Keywords: Communication; culture of communication